2001
DOI: 10.1159/000050639
|View full text |Cite
|
Sign up to set email alerts
|

Independent Factors Predict Supranormal CA 15-3 Serum Levels in Advanced Breast Cancer Patients at First Disease Relapse

Abstract: Data currently available are insufficient to demonstrate a real utility for CA 15-3 in the diagnosis, staging or surveillance of breast cancer patients following primary treatment. The aim of this study was to determine if there was a correlation between supranormal CA 15-3 serum levels and clinical and biological variables in breast cancer patients at first disease relapse. From October 1988 to March 1998, 430 consecutive patients entered the study. Overall CA 15-3 sensitivity was 60.7%. Elevated CA 15-3 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
2
8
0
4
Order By: Relevance
“…The incidence of the increase in CA 15-3 and CEA levels according to breast cancer molecular subtype may be useful in clinical practice. As regards the correlation between marker levels and metastatic site(s), the results thus far have been conflicting: Tampellini et al (16) reported that increased CA 15-3 levels were found more frequently in patients with liver metastases and in those with pleural effusion. Yerushalmi et al (20) did not identify significant differences in CA 15-3 and CEA levels between different sites of metastasis, whereas al-Jarallah et al (21) reported that the highest proportions of elevated CA 15-3 levels were found in patients with bone metastases and the highest proportions of elevated CEA levels in patients with lung, bone or liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the increase in CA 15-3 and CEA levels according to breast cancer molecular subtype may be useful in clinical practice. As regards the correlation between marker levels and metastatic site(s), the results thus far have been conflicting: Tampellini et al (16) reported that increased CA 15-3 levels were found more frequently in patients with liver metastases and in those with pleural effusion. Yerushalmi et al (20) did not identify significant differences in CA 15-3 and CEA levels between different sites of metastasis, whereas al-Jarallah et al (21) reported that the highest proportions of elevated CA 15-3 levels were found in patients with bone metastases and the highest proportions of elevated CEA levels in patients with lung, bone or liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the prognostic significance of an elevated CA15.3 and CEA in patients presenting with bone metastases has not been previously described. Several authors have commented on the correlation between overall tumour burden and CA15.3 levels (O'Hanlon et al, 1995;Tampellini et al, 2001). It is likely that elevated tumour markers reflect tumour burden in patients presenting with bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in CA15-3 level is most commonly observed in hormone receptor positive breast cancer (HR?) whereas the incidence of CA15-3 elevation is lowest in the HER2-enriched type of disease [15][16][17]. In addition, elevation of CA15-3 proved more common and pronounced in breast cancer with three or more metastatic sites, when compared to breast cancer with single metastasis and in patients with pleural metastasis at the time of diagnosis.…”
Section: Breast Cancermentioning
confidence: 96%